TRADISI ZIARAH KUBUR KE MAKAM KERAMAT RADEN AYU SITI KHOTIJAH DI DESA PEMECUTAN, KECAMATAN DENPASAR BARAT, KOTA DENPASAR BAGI UMAT HINDU DAN ISLAM - Alfian, Mohammad (Humanis; Volume 9. No. 1. Oktober 2014)
Pilgrimage grave tradition is an activity of Muslims and Hinduism on the occasion to commit the ancestor’s tradition. One of an activity of pilgrimage grave tradition is go to the Raden Ayu Siti Khotijah graves because she is a saint and Wali according to Muslims and Hinduism. This activity itself is just primer characteristics, and this tradition as secondary necessary or as a complement in ritual of Muslims and Hinduism. Raden Ayu Siti Khotijah’s tomb is an Islamic tomb in the middle of Hindu funeral. Problem of this study is limited of pilgrimage grave tradition, it has a ritual and and the impact to commit the pilgrimage grave for the society and pilgrim. In this research were qualitatively and Interpretative Descriptively analyzed based on the theory of Rudolf Otto, this theory was orientated for the people who love about supernatural thing so much. And market religion which is proposed by David Loy. The Raden Ayu Siti Khotijah tomb was believed as the tomb of Wali by Muslim pilgrims. But, for Hinduism was believed as a sacred tomb. Both of Muslim and Hindu were believed a myth of Raden Ayu Siti Khothijah tombs. in addition, there were various motivations to commit the pilgrimage grave and there were economic motivation, social, spiritual, health, and recreation.
Keywords: Pilgrimage, Hindu and Islam, Sacred Tombs